Raw material economy. Oil boom in Galicia (the second half of the 19th – the first half of the 20th century) - S.Z. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
With the beginning of the oil era in the world, Galicia with its oil fields got a chance to take part in the processes of globalization, and foreign capital along with technological innovations flowed into this previously unknown region. And many new jobs appeared in the oil industry for those Galician peasants who wanted to change their lives. However, even during the biggest oil boom at the beginning of the 20th century, the economy of Galicia could not go beyond the closed circle of the resource raw material model. One of the first oil entrepreneurs was Ignatius Lukasevich, who invented a way to obtain kerosene from oil, which was used for lighting. And one of the most famous oil tycoons was Stanislav Shchepanovskyi, the author of books on the economy of Galicia. His enterprises were located in Sloboda Rungurska, which became one of the main centers of oil production along with Drohobych and Boryslav. Moisei Hartenberg from Drohobych became another oil tycoon. Galician Ukrainians were not leaders in the oil business, they owned about 10 % of the deposits, and the rest were transferred to foreigners after the beginning of the oil boom. In general, during the oil boom, more than three hundred joint-stock companies related to this industry were founded in Galicia. Most of these were small-scale, and 15 major companies accounted for three-quarters of all oil production. Large companies were created by foreign investors. After all, the profit from investments reached at the end of the 19th century 10–12 % (in Western Europe it did not exceed 3–4 % at the time) due to low wages, as well as intensive development of deposits to obtain maximum income in a short time. The maximum level of oil production was reached in 1909 – but only 5,2 % of the world (in the USA at that time – 63 %). In general, the oil reserves in Galicia were not very large, and after the First World War, when most of the oil wells were destroyed, they were no longer restored.